Raman Spectroscopic Characterization of Environmentally Friendly Binder Systems for Carbon‐Bonded Filters. Issue 2 (31st July 2021) - Brehm, Simon; Himcinschi, Cameliu; Kraus, Jakob; Bock-Seefeld, Benjamin; Aneziris, Christos; Kortus, Jens
Abstract : A contribution to the production of zero‐defect materials is the development of carbon‐bonded alumina foam filters for removing nonmetallic inclusions from molten metals. Herein, such filters containing various mixtures of Carbores P, lactose, and tannin as binder are investigated by Raman spectroscopy. The filter samples differ in whether or not they are fired and whether or not n‐Si is added to them. Raman measurements are also performed on samples of the individual binder substances, which have been preannealed at temperatures up to 1400 °C. The variation of the sp 2 carbon cluster sizes due to the heat treatment is estimated using the intensity ratio of the D and G bands as determined from these measurements. The conversion of the samples from hydrogen‐rich amorphous carbon systems to nanocrystalline graphite is observed. The results show no significant differences between the binders in regard to the material properties that can be studied with Raman spectroscopy. Abstract : Herein, carbon‐bonded alumina filters for removing nonmetallic inclusions from molten metals as well as the binders Carbores P, lactose, and tannin are investigated by Raman spectroscopy. The variation of the sp 2 carbon cluster sizes during the firing process of the filters is estimated. The conversion of the samples from hydrogen‐rich amorphous carbon systems to nanocrystalline graphite is observed.